2016
DOI: 10.1155/2016/5467643
|View full text |Cite
|
Sign up to set email alerts
|

Multiple-Fault Detection Methodology Based on Vibration and Current Analysis Applied to Bearings in Induction Motors and Gearboxes on the Kinematic Chain

Abstract: Gearboxes and induction motors are important components in industrial applications and their monitoring condition is critical in the industrial sector so as to reduce costs and maintenance downtimes. There are several techniques associated with the fault diagnosis in rotating machinery; however, vibration and stator currents analysis are commonly used due to their proven reliability. Indeed, vibration and current analysis provide fault condition information by means of the fault-related spectral component iden… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
47
0
2

Year Published

2018
2018
2023
2023

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 69 publications
(49 citation statements)
references
References 40 publications
0
47
0
2
Order By: Relevance
“…In [15,16], wavelet analysis is also used in PMSM fault diagnosis. A method based on a variety of signals has been used in the fault diagnosis of induction motors [17]. Some studies [18,19] adopt the method of fusion of stator current, vibration and noise signals, and detect the short circuit fault based on the signal spectrum increment.…”
Section: Introductionmentioning
confidence: 99%
“…In [15,16], wavelet analysis is also used in PMSM fault diagnosis. A method based on a variety of signals has been used in the fault diagnosis of induction motors [17]. Some studies [18,19] adopt the method of fusion of stator current, vibration and noise signals, and detect the short circuit fault based on the signal spectrum increment.…”
Section: Introductionmentioning
confidence: 99%
“…By using Equations (4), (7), and (8), the drive signal can be explicitly calculated point-by-point in an analytical way. Compared to the look-up table and phase iterative calculating algorithms, it can significantly improve the unsteady state problem of the drive signal.…”
Section: Drive Synthesis For Multi-source Excitationmentioning
confidence: 99%
“…Furthermore, the vibration may also impact the structure life-time, component reliability, vehicle comfort, etc. The topics regarding collecting and analyzing the vibration and noise signals at some reference points for faulty diagnosis [2][3][4], power system health monitoring [5,6], structure modal analysis [7][8][9][10][11], and noise and vibration control [12][13][14] have been popular for decades. From this literature, it is also shown that in some circumstances of faulty diagnosis and noise control, the key information contained in the vibration and noise signals are presented as some special combinations of sinusoidal signals.…”
Section: Introductionmentioning
confidence: 99%
“…They are used for various types of machines and faults. Faults of electrical rotating motors (stator faults, rotor faults, broken rotor bar, ring cracking, bearing failures, rotor shaft failure, air-gap irregularities, broken teeth on sprocket) can be diagnosed by vibration [1][2][3][4][5][6][7][8][9][10][11][12] and acoustic signals [13][14][15][16][17][18][19][20][21][22]. Electric current analysis [23][24][25][26][27][28][29][30][31] and thermal analysis [32][33][34] are mostly used for limited faults, such as stator faults, rotor faults, and bearing failures.…”
Section: Introductionmentioning
confidence: 99%